(untitled) (American Journal of Islam and Society, 1993)
E. F. Schumacher, the author of Small Is Beautifit said, "We are at war with Nature and if by chance we win the war, we shall be the loser." This paradox of modem humanity is not universally accepted. However, there is hardly any visible sign of a deceleration in humanity’s unilateral war against the environment. Consequently, humanity is drawing closer and nearer to an imminent debacle. Although "the voices of peace" for solving the crisis could be heard as early as the late 194Os, their mediation has come to be regarded as valuable only recently. As a result, the global environmental movement has started shaping the course of developmental strategies. But, unfortunately, the growing concern over environmental devastation is still superficial and not viewed holistically. The ongoing concerns are limited to the extent of the exploitation of natural murces and the sustainability of the developmental processes. However, a few voices that consider the predicament from a holistic viewpoint and in a perspective of "deep ecology" are certainly audible in the global debate. The proponents of the holistic approach feel that humanity’s present awareness of the environmental crisis is not sufficient. What is needed, according to them, is a dispassionate ecological consciousness emanating from the synthesis of the complete experience of humanity since the dawn of civilization and also taking into consideration all facets of the ultimate reality. The New Ecological Realism For quite some time, a relational perspective has been stressed in discussions about understanding and solving the ecological crisis. According to this viewpoint, "nature is a web of relations" and therefore "denial of relationality is denial of being" (Skolimowski 1991). Furthermore, it expands the frontiers of the relationality of the human community to the greater relationality of all biotic and abiotic members of the biosphere and beyond. A concept of "the cosmic family" has been envisaged by advocates of this vision, and humanity is expected to mold its behavior patterns so that human beings can fulfill their obligations towards the vast family and honor all relations while deriving benefits from the esource pool of their cultural and physical environments. In its wake, a movement for deep ecology has been proposed. The term "deep ecology" signifies the encouragement of a more profound ...